(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Elena S. Milkevich (Southern Federal University. Rostov on Don, Russian Federation) The article focuses on metonymy as a linguistic device. Traditionally metonymy is considered within the domain of stylistics. However, methods of cognitive linguistics help to penetrate into the essence of language phenomena and explain their nature as part f more general process of human cognition. Cognitive linguistics puts forward the hypothesis that the use of metonymy is governed by cognitive principles. They are based on our experience, perception and culture. The article presents a study of metonymy in political headlines and analyses the application of cognitive principles to metonymy. We analyse the cases of metonymy presented by proper nouns geographical names such as names of countries, capital, continents. We come to the conclusion that the concept «COUNTRY» is the metonymic vehicle in three types of models: most frequent types of metonymy are: «COUNTRY FOR ITS GOVERNMENT», «COUNTRY FOR EVENT» and «COUNTRY FOR ACTION». The concept «COUNTRY» can also be the target in metonymy types «CAPITAL FOR COUNTRY» and «CONTINENT FOR COUNTRIES». The leading cognitive principles in such types of metonymic relationships are: based on human experience «CONCRETE OVER ABSTRACT», «INERACTIONAL OVER NON-INTERACTIONAL»; based on perceptual selectivity «DOMINANT OVER LESS DOMINANT», «MORE OVER LESS»; based on cultural preference «CENTRAL OVER PERIPHERAL», «MORE IMPORTANT OVER LESS IMPORTANT». Keywords: stylistics, metonymy, cognitive linguistics, cognitive principles, metonymic relationships. DOI 10.23683/1995-0640-2017-2-144-152